Telemedicine as tool: towards fulfilling South Africa's legal obligations around access to medical abortion - Brain, Grace (Department of Public Law, 2025)
South Africa's non-fulfilment of its legal obligations to provide abortion access to its population was only worsened by the COVID-19 pandemic. Despite the potential utility of medical abortion via telemedicine for the duration of the pandemic and beyond, health authorities in South Africa have not explicitly permitted the practice. This thesis asks whether medical abortion via telemedicine could be a useful tool in improving the state's fulfilment of its legal obligations around abortion access. It also discusses necessary limitations and regulations for medical abortion via telemedicine. This thesis is a desktop analysis, using published government, non-governmental organisation, and academic data and information. These were used to establish the legal obligations of the South African state regarding the provision of access to abortion; briefly assess the extent of fulfilment of these obligations; evaluate the potential utility of medical abortion via telemedicine in this context; and make recommendations for limitations and regulations on the practice of medical abortion via telemedicine. This work determines that, due to the significant lack of access to abortion services for the South African population, the state is in violation of its legal obligations around access to abortion. Moreover, medical abortion via telemedicine could be a useful tool in improving the fulfilment of these obligations. The implementation and scaling-up of medical abortion via telemedicine in South African public healthcare is therefore recommended, with necessary oversight and limitations. These findings demonstrate that increased fulfilment of South Africa's legal obligations around access to abortion may be possible. The state must act to increase fulfilment through implementing relevant recommendations, such as legislative amendments and the initiation of future programmes providing medical abortion via telemedicine. Moreover, health authorities in South Africa must amend their telemedicine guidelines, making the guidelines practical, evidence-based, and reasonably permissive of accepted medical practices such as medical abortion via telemedicine.